A Simplified Working Classification Proposed for Myxoid Tumors of Oral Cavity - Manas Bajpai; Nilesh Pardhe (Iranian Society of Pathology, 2017)
Dear Editor-in-Chief Myxoid tumors of oral cavity encompass a broad spectrum of lesions, primarily neoplastic.(1) The significant variations in the biological behaviour; ranging from completely harmless to malignant neoplasm they require an accurate histopathological diagnosis to ensure a proper treatment. (2) Because of the considerable overlapping between the clinical and histopathological features, this group of tumors often produce a diagnostic difficulty to the clinicians and oral pathologists.(3) An exhaustive review of the literature reveals that there is no approved classification of myxoid tumors of oral cavity. A simple working classification of myxoid tumors is proposed here.